Rancang Bangun Sistem IoT Berbasis Energi Hibrid untuk Pemantauan Real-Time dan Peringatan Dini Banjir Rob Pesisir - Al Haris, Firdhaus Hari Saputro; Wisudawanto, Rahmat; Fathin Wahyu Lestari, Azizun (Jurnal Algoritma, 2025)
Tidal flooding is a chronic problem in the coastal areas of Semarang that requires a reliable, real-time monitoring system. This study aims to design, build, and test a prototype Internet of Things (IoT) system for tidal flood monitoring that can operate in coastal environments with limited infrastructure. The research method used is Research and Development (R&D), which includes needs analysis, system design, implementation, and experimental testing. The resulting prototype consists of an HC-SR04 ultrasonic sensor, an Arduino Nano microcontroller, and a NodeMCU ESP8266 communication module supported by a hybrid energy source of a 100-watt solar panel and a 12V 8Ah battery. The measured data is sent to the server and visualized on the web dashboard https://pasutmaritimsmg.store/dashboard.php and sent as an early warning notification via the Telegram application. The test results show that the system has a measurement accuracy of plus or minus 0.25 cm with a data delivery success rate of 98.2%. The system can operate independently for more than 5 days without sunlight. Validation with data from the Indonesian Meteorological, Climatological, and Geophysical Agency (BMKG) shows a very high correlation (R² = 0.98). It is concluded that this prototype is effective as a real-time tidal flood monitoring solution and can be further developed to support an integrated early warning system.